Teaching methods for motivating girls to learn science subjects in community secondary schools in Mbeya, Tanzania - Toto, Stella F.; Mngarah, Daniel M.; Bwagilo, Huruma O. (Papers in Education and Development, 2024)
This qualitative study investigated effective teaching methods that motivate girls to learn science subjects in community secondary schools in Mbeya, Tanzania. It focused on participants’ perspectives on these methods and the challenges teachers face in the teaching process. Data were collected from 40 participants across four community secondary schools using observations, interviews, and focus group discussions. The findings revealed that teachers used both teacher-centred and learner-centred approaches to motivate girls to learn science subjects. However, challenges such as overcrowded classrooms, inadequate teaching resources, and poor infrastructure hindered teachers’ efforts to motivate girls to learn science. The study recommends improving the learning environment and resource availability to enhance girls’ motivation and engagement in science subsects within community secondary schools.